2012
DOI: 10.1590/s0073-47212012005000006
|View full text |Cite
|
Sign up to set email alerts
|

Space-time variation of the relative abundance of Limnoperna fortunei in deep zones of São Gonçalo Channel, Rio Grande do Sul, Brazil

Abstract: ABSTRACT. This work describes the spatial-temporal variation of the relative abundance and size of Limnoperna fortunei (Dunker, 1857) collected in São Gonçalo Channel through bottom trawl with a 0.5 cm mesh, at depths between 3 and 6 m. The estimative of mean relative abundance (CPUE) ranged from 2,425.3 individuals per drag (ind./drag) in the spring to 21,715.0 ind./drag in the fall, with an average of 9,515.3 ind./drag throughout the year. The estimated mean density of L. fortunei for the deep region of Sã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Among larvae collected, the D‐shaped and veliger forms accounted for the largest proportion. Lopes & Vieira (2012) reported the spatial–temporal variation of L. fortunei in São Gonçalo Channel in Brazil by sampling seasonally via bottom trawl at 3 ~ 6‐metre depths. They suggested that the evaluated average density of L. fortunei in the deeper areas of the channel was 1.2 to 10.3 ind./m 2 , with a maximum density of 84.9 ind./m 2 in autumn.…”
Section: Distribution and Population Dynamics Of Limnoperna Fortuneimentioning
confidence: 99%
“…Among larvae collected, the D‐shaped and veliger forms accounted for the largest proportion. Lopes & Vieira (2012) reported the spatial–temporal variation of L. fortunei in São Gonçalo Channel in Brazil by sampling seasonally via bottom trawl at 3 ~ 6‐metre depths. They suggested that the evaluated average density of L. fortunei in the deeper areas of the channel was 1.2 to 10.3 ind./m 2 , with a maximum density of 84.9 ind./m 2 in autumn.…”
Section: Distribution and Population Dynamics Of Limnoperna Fortuneimentioning
confidence: 99%
“…The golden mussel has shown great dispersal potential in Brazil, and its presence has already caused substantial impacts on community structures and ecosystem functioning (Lopes et al, 2009;Lopes & Vieira, 2012) as well as economic damage (Darrigran et al, 2020) in the region. The rst occurrence of L. fortunei in Brazil dates back to 1999 (Mansur et al, 1999).…”
Section: Introductionmentioning
confidence: 99%